1994
DOI: 10.2136/sssaj1994.03615995005800020021x
|View full text |Cite
|
Sign up to set email alerts
|

Stability Constants of Pseudobactin Complexes with Transition Metals

Abstract: The stability constants of the fluorescent siderophore pseudobactin St3 (PSB3) produced by Pseudomonas putida strain 3 with Fe3, Cu2+, Mn2+, Zn2+, and Fe2+ were determined using fluorescence spectroscopy and potentiometric titrations. Stability constants for PSB3, with Fe3+, Fe2+, Mn2+, and Zn2+ were determined based on titration to saturation of a PSB3 ligand solution with either of the metals, then back‐titrating the solution with an EDTA solution along with simultaneous measurements of fluorescence and visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…PSB has a K,,, of 22.5 at pH 6.0, 25"C, and 0.1 M ionic strength (Chen et al, 1994). It was found that ligand exchange from FePSB to MA did not occur at all, whereas a complete exchange from FeMA to PSB occurred with a half-life of 2 h (Jurkevitch et al, 1993).…”
Section: Discussionmentioning
confidence: 95%
“…PSB has a K,,, of 22.5 at pH 6.0, 25"C, and 0.1 M ionic strength (Chen et al, 1994). It was found that ligand exchange from FePSB to MA did not occur at all, whereas a complete exchange from FeMA to PSB occurred with a half-life of 2 h (Jurkevitch et al, 1993).…”
Section: Discussionmentioning
confidence: 95%
“…This is not surprising since it is well established that vanadium can be liganded by hydroxamates, carboxylates and catecholates (Keller et al, 1991 ;Rehder, 1991). Others have also demonstrated the fact that PVD, as well as PCH, can complex copper, zinc or manganese (Poppe et al, 1987 ;Chen et al, 1994 ;Visca et al, 1992 ;Bouby et al, 1999). Visca et al (1992) suggested that PCH could play a role in the acquisition of metals other than Fe(III), such as Co(II) and Mo(VI).…”
Section: Discussionmentioning
confidence: 96%
“…monads has increased recently because of the possible use of siderophores as biopesticides (Wilson, 1997) and the possible use of pseudomonads in detoxifying chemical wastes through a wide range of enzymatic metabolic activities (Raaijmakers, 1995). Iron metabolism has also been studied because of the potential role of microbial siderophores in facilitating uptake of heavy metals and their mobilisation under certain growth conditions (Chen et al,1994;Mench et al, 1994 ). Here, we have investigated the specific stimuli for siderophores production in local strains of P. fluorescens under different Fe (III) concentrations in the presence of various carbon sources.…”
Section: Introductionmentioning
confidence: 99%